2012
DOI: 10.4238/2012.september.26.7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an association between TSC gene Arg904Gln polymorphisms and essential hypertension risk based on a meta-analysis

Abstract: ABSTRACT. Although there have been several studies investigating a possible association between essential hypertension and TSC gene Arg904Gln polymorphisms, the results have been inconsistent. We conducted a meta-analysis of four case-control studies (one study in Europe and three studies in Asia), including 1811 essential hypertension cases and 1381 controls. The pooled results showed no significant associations between any of these polymorphisms and essential hypertension (allele Arg vs allele Gln: odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, other studies have not found correlation between SLC12A3 polymorphisms and hypertension. Zhang et al [17] have reported the lack of association between Arg904Gln substitution and essential hypertension based on a meta-analysis, while other studies did not observe the relationship of reported SLC12A3 polymorphisms with hypertension in rats [18] and humans [19]. Similarly, the Arg904Gln polymorphism in NCC did not show correlation with hypertension, as evidenced by the investigation of two ethnic groups in Northwest China [20] and our earlier study in the Uyghurs, Kazaks, and Mongolians [21], ethnic minorities in China.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have not found correlation between SLC12A3 polymorphisms and hypertension. Zhang et al [17] have reported the lack of association between Arg904Gln substitution and essential hypertension based on a meta-analysis, while other studies did not observe the relationship of reported SLC12A3 polymorphisms with hypertension in rats [18] and humans [19]. Similarly, the Arg904Gln polymorphism in NCC did not show correlation with hypertension, as evidenced by the investigation of two ethnic groups in Northwest China [20] and our earlier study in the Uyghurs, Kazaks, and Mongolians [21], ethnic minorities in China.…”
Section: Introductionmentioning
confidence: 99%